Impact of Moderate Aerobic Training on Physical Capacities of Hypertensive Obese Elderly - Raphael Miranda Ramos GD; Hélio José Coelho-Júnior DSt; Ricardo Yukio Asano PhD; Raul Cosme Ramos Prado MSt; Rodrigo Silveira MSt; Christiano Bertoldo Urtado PhD; Leonardo Coelho Rabello de Lima PhD; Samuel da Silva Aguiar DSt; Jonato Prestes PhD; Alexandre Igor Araripe Medeiros PhD; Bruno Rodrigues PhD; Claudio de Oliveira Assumpção PhD (Gerontology and Geriatric Medicine, 2019)
The association of old age and chronic conditions, such as hypertension and obesity, can lead to larger decreases in the physical capacities of elderly, compared with their healthy counterparts. Physical exercise has been demonstrated to be efficient in postponing this phenomenon, mainly strength training. However, little is known about the effect of aerobic training on this condition. The aim of this work was to investigate the impact of 12 weeks of moderate-intensity aerobic training on the physical capacities of hypertensive obese older women. Aerobic power, lower limb muscle power, upper limb muscle strength, endurance, and flexibility of 19 hypertensive obese elders were evaluated. Afterward, patients were blindly randomized into control group (CG) and exercise group (EG). EG underwent three sessions/week of 60 min of moderate-intensity aerobic training, during 12 weeks. EG showed increases in VO 2max compared with CG ( p = .03) and increases in flexibility compared with basal moment (+21.6%; p = .01) after 12 weeks, whereas CG did not show any significant alterations. Moderate aerobic training is capable of inducing increases in maximal aerobic power and flexibility in hypertensive obese elderly. However, other essential physical capacities associated with independence in elderly people (i.e., muscle power and strength) were not responsive to this kind of protocol.